Exploring symbolism in Hu Ru Gui by Malaysian Chinese writer Dai Xiaohua among Chinese tertiary students - Shi Shao Hua; Revathi Gopal (Universitas Syiah Kuala, 2024)
This article explores English literature teaching, particularly the application of symbolism in a literary work called Hu Ru Gui among Chinese tertiary students majoring in English. Hu Ru Gui is a novel written by a Malaysian Chinese writer, Dai Xiaohua, which then became one of the literature teaching materials used at the tertiary level for Chinese students. This paper discusses the spiritual bloodline themes in the form of symbolism which runs through the whole literature work. The themes range from attitudes towards life and death, the national ridge of defending the motherlands dignity, and the patriotic values internalized deeply from generation to generation beyond time, location, and culture. A qualitative method was employed in the current study. Purposive sampling was used to select five students to participate in the study. The students were at the advanced level of English language proficiency. An interview protocol was applied as an instrument to collect data from a semi-structured interview. The feedback from the tertiary students was analysed through thematic analysis in the forms of themes, sub-themes, and codes. The research results revealed that the traditional values and patriotic values in the form of symbolism in Hu Ru Gui, the novel rooted in culture are the seeds of the motherland. Wherever and whenever a person goes, the seeds will bloom and inherited. Future research can focus on exploring how the themes, motifs, and symbols within the text resonate with Chinese tertiary students in Malaysia.